ASPEK SOSIAL EKONOMI TUMPANGSARI HUTAN DI KESATUAN PEMANGKUAN HUTAN (KPH) CIAMIS WILAYAH DAERAH ALIRAN SUNGAI (DAS) CITANDUY - Rachman Effendi; Akub J Abdurachman (Jurnal Penelitian Hasil Hutan (Journal of Forest Products Research), 2017)
One  of planting  pattern   in reforestation   that  has proved   to  be successful   is  taungya   system.   The  advantage gained by  the  farmers  are especially  in the  fulfilment  of  food  need  in  the short  term.